A Geometric Solution to the Jacobian Problem - Kerimbayev Rashid Konyrbayevich (Journal of New Theory)
In this article given a geometric solution to the well-known Jacobian problem. The twodimensionalpolynomial Keller map is considered in four-dimensional Euclidean space R4. Used the conceptof parallel. A well-known example of Vitushkin is also considered. Earlier it was known that Vitushkin’s maphas a nonzero constant Jacobian and it is not injective. We will show that the Vitushkin map is not surjectiveand moreover it has two inverse maps in the domain of its definition